Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: "Choice is My Right" "No Anti-Abortion Amendment" "A Women's Life is a Human Life"